2010
DOI: 10.1007/s00542-010-1151-4
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of GaN light emitting diode membrane on Si substrate for MEMS applications

Abstract: GaN membrane structures are fabricated for micro-electro-mechanical systems (MEMS). The combination of GaN and Si semiconductors is promising for future MEMS. However, due to the different material properties, the fabrication of MEMS using GaN semiconductor is still limited. Here, a simple membrane of GaN semiconductor deposited on Si substrate was investigated. The GaN crystal was grown by molecular beam epitaxy and metal organic chemical vapor deposition. The basic properties of the fabricated GaN light emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The proposed configuration can be fabricated through GaN-on-silicon platform. The fabrication of freestanding structure on GaN-silicon platform is a mature technology which has been widely reported in LED radiation pattern [28], [29] and enhance light extraction [30], [31]. TiO2 micro-nano structure etching is compatible with GaN, it has been used as high contrast grating reflector in GaN-VCSELs [32].…”
Section: Laser Design and Athermal Propertiesmentioning
confidence: 99%
“…The proposed configuration can be fabricated through GaN-on-silicon platform. The fabrication of freestanding structure on GaN-silicon platform is a mature technology which has been widely reported in LED radiation pattern [28], [29] and enhance light extraction [30], [31]. TiO2 micro-nano structure etching is compatible with GaN, it has been used as high contrast grating reflector in GaN-VCSELs [32].…”
Section: Laser Design and Athermal Propertiesmentioning
confidence: 99%
“…The light generation in both, conventional LED (Wakui et al 2011) and OLED, is because of recombination of electrons and holes. Still, there are a lot of differences in them ranging from architecture to carrier transport, and processes governing recombination rate.…”
Section: Oled Architecturementioning
confidence: 99%
“…Aiming to solve the aforementioned issues, various approaches have been presented, such as micro-and nano-patterned surface texturing, antireflective coating layers, photonic crystals and so on [13]- [18]. Recently, Hane et al reported the removal of silicon substrate from the backside to form a free-standing GaN membrane offering much more manufacturing flexibilities for MEMS applications [19]. There is a potential for increasing the light extraction efficiency and improving the electrical performance of LED on GaN-on-silicon platform by using free-standing GaN membrane.…”
Section: Introductionmentioning
confidence: 99%